The Dark Pigment in the Sesame (Sesamum indicum L.) Seed Coat: Isolation, Characterization, and Its Potential Precursors - Dossou, Senouwa Segla Koffi; Luo, Zishu; Wang, Zhijian; Zhou, Wangyi; Zhou, Rong; Zhang, Yanxin; Li, Donghua; Liu, Aili; Dossa, Komivi; You, Jun; Wang, Linhai (Frontiers in Nutrition, 2022)
Sesame is a worldwide oilseed crop used in the food pharmacy. Its seed phenotypes determine the seed quality values. However, a thorough assessment of seed coat metabolites is lacking, and the dark pigment in the seed coat is not well characterized. Herein, we report the isolation of melanin by the alkali method from the black and brown sesame seeds. Physicochemical methods, including scanning electron microscopy (SEM), solubility, precipitation, UV-Vis spectroscopy, Fourier transform infrared (FT-IR) spectroscopy, and thermogravimetric-differential scanning calorimetry (TG-DSC), were used to characterize the sesame melanins. The results clearly showed that the isolated pigments were similar to melanin from other sources. Both melanins were heat-stable and exhibited numerous characteristic absorption peaks. Through a comprehensible LC-MS/MS-based metabolome profiles analysis of NaOH and methanol extracts of black and white sesame seeds, caffeic, protocatechuic, indole-carboxylic, and homogentisic acids were identified as the potential precursors of the sesame melanin. Our findings widen our understanding of dark seeds pigmentation in sesame. Furthermore, they show that black sesame seeds are promising sources of edible melanin for food and biotechnological applications.